2019
DOI: 10.1080/1331677x.2019.1633943
|View full text |Cite
|
Sign up to set email alerts
|

Macro determinants of shadow banking in Central and Eastern European countries

Abstract: Our study aims to quantitatively assess some of the determinants of shadow banking dynamics in 11 European Union (E.U.) countries from Central and Eastern Europe (C.E.E.) over the period 2004-2017. Using panel data estimation techniques and a quarterly data set compiled from several publicly available data sources, we alternatively evaluate the impact of six macroeconomic and financial variables on two dependent variables corresponding to two different measures of the shadow banking sector, namely the broad on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…The limited number of studies on the topic suggests scope for further exploration of factors leading to the development of SB. As suggested by Apostoaie and Bilan (2020) and Hodula et al (2017), the impact of regulative arbitrage opportunities on SB could be addressed in this regard. Consistent with Kou et al (2021a), our study suggests that country-specific analyses can provide essential recommendations for improving the financial systems of particular countries.…”
Section: What Drives Sb In Economies?mentioning
confidence: 96%
See 1 more Smart Citation
“…The limited number of studies on the topic suggests scope for further exploration of factors leading to the development of SB. As suggested by Apostoaie and Bilan (2020) and Hodula et al (2017), the impact of regulative arbitrage opportunities on SB could be addressed in this regard. Consistent with Kou et al (2021a), our study suggests that country-specific analyses can provide essential recommendations for improving the financial systems of particular countries.…”
Section: What Drives Sb In Economies?mentioning
confidence: 96%
“…Independent variables comprised real GDP growth rate, term spread, the growth rate of the total financial assets of pension funds and insurance corporations, money market interest rate, growth rate of the total reserves (excluding gold), and the growth rate of the total assets reported by the Monetary Financial Institutions (as defined by the European Central Bank). Apostoaie and Bilan (2020) found that developments in the traditional banking sector, institutional investors sector, and money market interest rate, overall liquidity and economic conditions influence the SB sector positively. Term spread, however, was found to negatively influence the SB sector.…”
Section: Determinants Of Sbmentioning
confidence: 99%
“…The core determinants selected in our model have been previously used in academic literature (Kim, 2016;Barbu, Boitan and Cioaca, 2016;Apostoaie and Bilan, 2019) Considering the definitional ambiguities of the shadow banking system (SBS), it is difficult to empirically map the dependent variable. As already mentioned, there has not been an internationally harmonised definition of SBS for a sufficiently long period.…”
Section: Datamentioning
confidence: 99%
“…Hence, when specifying the econometric model and selecting the variables, we had to search for an 'appropriate' measure of the size of shadow banking that would be comparable across the selected group of countries. In empirical terms, we followed the approach by Kim (2016) and Apostoaie and Bilan (2019) to define the size of a shadow banking system as the value of the total assets of other financial intermediaries (OFIs), expressed as a percentage of the GDP.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation